2002
DOI: 10.1021/jm0208774
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Antitumor Activity of Novel Ring D Analogues of the Marine Pyridoacridine Ascididemin: Structure−Activity Relationship

Abstract: Marine compounds with pyridoacridine skeletons are known to exhibit interesting antitumor activities. Ascididemin has already been reported as displaying significant antitumor activities in vitro and has also been found to have a relatively high global toxicity in vivo. We synthesized a series of 16 analogues (among which 11 compounds were different from previously described ones) with the aim of developing new anticancer agents with significantly improved efficacy/tolerability ratios. These compounds were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…), 4) chemical synthesis, [19] 5) structure-activity relationship (SAR) studies for drug optimization, [20,21] and finally, 6) assurance of a homogeneous supply of the compound for preclinical and clinical trials. [22,23] Each of these stages is crucial in the development of a drug.…”
Section: Introductionmentioning
confidence: 99%
“…), 4) chemical synthesis, [19] 5) structure-activity relationship (SAR) studies for drug optimization, [20,21] and finally, 6) assurance of a homogeneous supply of the compound for preclinical and clinical trials. [22,23] Each of these stages is crucial in the development of a drug.…”
Section: Introductionmentioning
confidence: 99%
“…The quinoline‐5,8‐dione employed in Scheme was also used in the synthesis of non‐natural analogues 117 (Scheme ) . The quinone was treated with various ortho ‐aminoacetophenones 114 to provide variation in the benzene ring, and the products 115 closed to tetracycles 116 with strong acid.…”
Section: Pyrido[234‐kl]acridinementioning
confidence: 99%
“…In a study conducted by Delfourne and co-workers in [45] , ascididemin analogues were synthesized and evaluated for their cytotoxic potential by MTT assay. Some ascididemin analogues (ring D-modified) appeared to be more cytotoxic than the reference compound ascididemin ( Table 2 ).…”
Section: Ascididemin Analoguesmentioning
confidence: 99%
“…Some ascididemin analogues (ring D-modified) appeared to be more cytotoxic than the reference compound ascididemin ( Table 2 ). Furthermore, it was reported that substitution at R 1 and R 3 does not have much influence on cytotoxic activity [45] .…”
Section: Ascididemin Analoguesmentioning
confidence: 99%
See 1 more Smart Citation